Methods for Revealing the Metacognitive Knowledge of Adolescent Information Seekers During the Information Search Process - Bowler, Leanne (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This paper describes the methods used to investigate the metacognitive knowledge of adolescents, aged 16 to 19, as they searched for, selected and used information for a school-based inquiry project. The study has implications for information literacy instruction and contributes to the understanding of adolescent information-seeking behavior. Cette communication décrit les méthodes utilisées pour explorer les connaissances métacognitives d’adolescents, âgés de 16 à 19 ans, lors de la recherche, la sélection et l’utilisation d’information pour un projet de recherche scolaire. Cette étude a des répercussions sur l’enseignement de la culture informationnelle et contribue à la compréhension du comportement de recherche d’information des adolescents.